Personal injury awards: the impact of income tax on damages for loss of earning capacity - Van Niekerk, Marc George (Department of Commercial Law, 2023)
It is a vexed question internationally whether, in personal injury actions, damages are awarded for lost earnings or lost earning capacity. As will be more fully discussed in due course, both the case law and the general practice of the courts are inconsistent, with wholesale acceptance of either "concept", and both judges and academic writers are guilty of indiscriminate use of both terms whilst espousing support for one or other concept. It will be submitted that the South African authorities favour the concept of loss of earning capacity, in line with the international trend. Whether or not this distinction should or does have practical implications will be considered and debated. Given, however, the inconsistency mentioned above, the writer will be unable to make reference to only one or other of the generally accepted terms and the reader is accordingly requested to bear this in mind.